Design And Study Of Domestic Cooling System Through Roof Ventilation Assisted By Evaporative Cooling - Teoh, Jing Xiang (Universiti Sains Malaysia, 2018)
There is an increasing trend of demand of air conditioning increase to achieve thermal comfort of human due to urbanization of the world in the future. An alternative way is introduced to achieve the thermal comfort which is reducing the amount of heat flux from house’s roof. Hence, a CS with combination of natural ventilation, force ventilation and water evaporation is designed to achieve cooling process with low water consumption and low electricity consumption. A scale – down prototype and test house is built to test the performance of the CS. 4 thermocouples are installed to two section of test house to measure temperature. The test house is placed in the sun from 10am to 3pm of a day for experiments. The performance of the cooling device was measured by comparing the temperature difference between two sections of the test house which only one of the sections is installed with CS. Model of scale – down prototype and actual size of CS is built for the simulation to investigate the performance of the DCS and compare the result of the experiment. The experiment results show that the section with CS of test house is cooler than the section without CS up to 5.97℃. Result shows that CP is increase as the reference temperature increase. The Result also shows that cooling duct with difference air speed is performed well in difference range of reference temperature. The result of the simulation shows that the highest CP is shown as the air speed condition is low (1m/s) for all heat source conditions. The difference among the theoretical calculation, experimental result and simulation results are due to the difference of performance of mist spray nozzle. It can be concluded that a good DCS is designed. It can performance well (up to 5.97℃) with low water consumption and low electricity consumption.